Ideal Dalam Semigrup Ternari Komutatif - Noverly Cloren Pattinasarany (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Pattimura University, Ambon, Indonesia, 2020)
Algebra is a branch of mathematics that deals with mathematical objects (say, numbers with no known exact value), and uses symbols such as x and y to study them. In algebra, the properties possessed by the operations that can be performed on the object (think addition and multiplication) are studied, and then become